6(2x+8)=4(3x+12)

Simple and best practice solution for 6(2x+8)=4(3x+12) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(2x+8)=4(3x+12) equation:


Simplifying
6(2x + 8) = 4(3x + 12)

Reorder the terms:
6(8 + 2x) = 4(3x + 12)
(8 * 6 + 2x * 6) = 4(3x + 12)
(48 + 12x) = 4(3x + 12)

Reorder the terms:
48 + 12x = 4(12 + 3x)
48 + 12x = (12 * 4 + 3x * 4)
48 + 12x = (48 + 12x)

Add '-48' to each side of the equation.
48 + -48 + 12x = 48 + -48 + 12x

Combine like terms: 48 + -48 = 0
0 + 12x = 48 + -48 + 12x
12x = 48 + -48 + 12x

Combine like terms: 48 + -48 = 0
12x = 0 + 12x
12x = 12x

Add '-12x' to each side of the equation.
12x + -12x = 12x + -12x

Combine like terms: 12x + -12x = 0
0 = 12x + -12x

Combine like terms: 12x + -12x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| x+0.5x=13.5 | | -5(1-x)-9x=4-5x | | 45=12t+3(t-8)-6 | | y-c=b | | 50-7x=8(x+10) | | x+(x+20)/4+(3x-50)/2+5(x-20)/4=195 | | ln(4)+ln(x+2)=ln(19) | | 3b+b=3 | | y-u=b | | -2+2x-3=-4x-5+6x | | 50+10m=4(8m-4) | | 4.1x-23=3.9x-1 | | x/3-7/12=2/3 | | 10-5(-2b+3)=b-5 | | 0.6g+0.5g=2.9 | | 25+125+13x=11 | | -21=a-47 | | 14.15h+0.07=14.65h-0.08 | | 4x+7=3x-5 | | (5-3i)(5+3i)= | | x+18=-13 | | 4+10r=8(5r+8) | | 30+44x=99+25x | | -7(-4+7x)=-70 | | 16+54x^3=0 | | 14.15+0.07h=14.65-0.08h | | -11.2+4(t+8.2)=37.5 | | 2x+2=8x+6x-25 | | .25=-7.15+-1y | | -g/24=5/12 | | y=(1)+4 | | 6(a+2)=6a+12 |

Equations solver categories